Phenolic profiles of andean mashua (Tropaeolum tuberosum Ruíz & Pavón) tubers: Identification by HPLC-DAD and evaluation of their antioxidant activity - Chirinos R. (2008)
Qualitative high performance liquid chromatography with diode array detection (HPLC-DAD) was performed to characterize nonanthocyanin phenolic compounds in three different coloured mashua genotypes. The ORAC antioxidant activity contribution in the tubers related to the type of phenolic compounds present was also evaluated. Phenolic compounds were analysed by separating them into four main fractions: fraction I obtained by means of a liquid–liquid partition with ethyl acetate and fractions II, III and IV obtained by elution on a Sephadex LH-20 column. Fraction I revealed the presence of gallic acid, gallocatechin, procyanidin B2 and epigallocatechin. Other phenolic compounds such as hydroxycinnamic and hydroxybenzoic acid derivatives, rutin and/or myricetin derivatives were also present in fraction I. Fraction II was mainly composed of epicatechin, hydroxycinnamic and hydroxybenzoic acid derivatives. Fraction III presented mainly anthocyanins for the purple coloured mashua tubers and rutin, hydroxycinnamic acid and hydroxybenzoic acid derivatives for the yellow coloured genotype. Fraction IV was composed of proanthocyanidins. Alkaline and acid hydrolysis of the different fractions revealed the presence of gallocatechin, epicatechin, p-coumaric acid, o-coumaric acid, cinnamic acid, protocatechuic acid, rutin and quercetin as the main phenolic moieties present. The proanthocyanidin fractions were the major contributors to the ORAC antioxidant activity of the mashua tubers for two of the three genotypes (34.7–39.2%). The results obtained in the present study confirm that mashua tubers constitute a promising source of antioxidant phenolics and could potentially be considered as a functional food with beneficial health effects.